ANALISIS KESALAHAN MORFOLOGI DALAM SURAT DINAS DI DINAS PENDIDIKAN KABUPATEN MAJENE, SULAWESI BARAT - Jerniati I.; Musayyedah Musayyedah; Ratnawati Ratnawati (Kantor Bahasa Provinsi Gorontalo, 2021)
The purpose of this study is to describe the use of the Indonesian language with a specific sequence of morphological errors in the official letter of the Majene Regency Education Office. This study uses structural linguistic theory with morphological error analysis. This brief research uses a descriptive-analytical method that explains what it is about research object data. The data comes from outgoing official documents archived by the administrative staff of the Dinas Pendidikan of Majene Regency.. The results showed that the frequency of morphological errors was most often found in the wrong choice of words (including non-standard words). The frequency of frequent errors in the construction of words formed by prefixes or confixes in one of the basic words. Word constructions with such prefixes are generally written separately from the basic words. On the contrary, writing a proposition, in general, is written a series. Then the frequency of errors that are being an inaccurate diction on the construction of the opening letter of the letter which generally begins with the word